Selection of portfolios of electricity generation projects : an exploratory study - Matos, Eduardo (2013)
The electricity planning traditionally relies on optimization models with the objective of minimizing system costs. However, the liberalization trend of the market and development of renewable energy increased the complexity of this planning exercise. It becomes then necessary to study other methodologies in order to include in the planning process the risk variables and potential correlation between technologies and fuels. The main guidelines of current energy policy in Portugal should meet the goals of energy efficiency, reduce energy dependence without compromising security of supply, minimizing the environmental impact and promoting renewable energy development. In a scenario of high growth of renewable energy sources (RES), it is pertinent to study the seasonality of electricity production by the various RES (biomass, hydro, wind, solar ...) evaluating the potential complementarily between these sources as a mitigation or increase risk factor. As for thermal power plants, the existence or not of correlation between fossil fuel prices must also be considered. The risk-return approach is often used in the selection of financial assets, however, several studies have revealed its potential when applied to electricity planning, especially with regard to the inclusion of RES projects. This study will test the possible application this model for the Portuguese electricity system, resulting in the proposal of future scenarios for the electricity generation sector taking into account the increasing importance of RES.